Analysis of Determinants of Economic Efficiency in Honey Production in Horo Guduru Zone, Ethiopia: Stochastic Dual Cost Frontier Model Approach - Tolesa Tesema; Megersa Adugna (Advances in Agriculture)
Honey production is generating employment and source of income in the rural area of Ethiopia. However, its productivity was low. The objective of this study was to measure the economic efficiency of honey production in Ethiopia’s Horo Guduru Wollega Zone and their limiting factors. To achieve the above-mentioned objective, the study employed a survey methodology using a structured questionnaire tool, and the data were collected from 396 households. Both descriptive and econometric data analysis methods are employed. Dual cost was used to measure the levels of economic efficiency and the Tobit model to identify the determinants of economic efficiency in the study area. In this regard, the analysis relied on a cross-sectional data collected from 396 sample farm households. The mean economic efficiency was 44%. This demonstrates that the farmers in the study area have to decrease production cost by 56% to achieve 100% economic efficiency level. From the determinants of economic efficiency family size, extension services, training, beekeeping experience, and family size are significant technical efficiency variables for honey producers. The study suggests policies to address economic inefficiencies by increasing the number of hives, extending the best performers’ experience by increasing the frequency of extension contacts on honey production, facilitating and expanding credit service in the study area, making bee forage access simple, and increasing forest coverage on the land area in line with the current policy of Ethiopia. Additionally, since farmers in the study area spend their time guarding the honey from damage by ants and monkeys, labor that utilizes technology must be made available in the study area.